2021
DOI: 10.1097/nmd.0000000000001462
|View full text |Cite
|
Sign up to set email alerts
|

Childhood Trauma Associations With the Interpersonal Psychological Theory of Suicide and Social Cognitive Biases in Psychotic Disorders

Abstract: Childhood trauma (CT) is associated with suicidal ideation and behaviors (SI/SB) in people with psychosis. The interpersonal psychological theory of suicide (IPTS) suggests that there are four factors that increase suicide risk: thwarted belongingness, perceived burdensomeness, acquired capacity for suicide, and hopelessness. The IPTS constructs and social cognitive biases are associated with SI/SB in psychotic disorders. However, the role of CT in IPTS constructs and social cognitive biases has not been exami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 54 publications
(97 reference statements)
0
13
0
Order By: Relevance
“…Two studies used the Ambiguous Intention Hostility Questionnaire (AIHQ). 40 , 55 While 1 study found that participants with SI had greater attributions of blame in ambiguous situations compared to those without SI, 40 the other included study found no relationship between the AIHQ blame subscale and lifetime SI. 55 It is possible that this discrepancy in findings is present as the study led by Depp et al assessed for current, not lifetime, SI.…”
Section: Resultsmentioning
confidence: 90%
See 4 more Smart Citations
“…Two studies used the Ambiguous Intention Hostility Questionnaire (AIHQ). 40 , 55 While 1 study found that participants with SI had greater attributions of blame in ambiguous situations compared to those without SI, 40 the other included study found no relationship between the AIHQ blame subscale and lifetime SI. 55 It is possible that this discrepancy in findings is present as the study led by Depp et al assessed for current, not lifetime, SI.…”
Section: Resultsmentioning
confidence: 90%
“…The primary objective of 10 of the studies examined the relationship between some aspect of social cognition and SI or behavior, 40–45 , 50–54 whereas 5 of the studies did not have a primary objective of examining this relationship and reported statistics examining the relationship. 33 , 39 , 46 , 47 , 55 Nine studies included purely cross-sectional analysis of social cognitive variables, 33 , 43–47 , 53–55 5 studies were longitudinal with follow-up intervals ranging from 2 weeks to 20 years, 39–41 , 51 , 52 and 2 studies were cross-sectional case-control designs. 42 , 50 One included study is a Letter to the Editor that contains empirical data not published elsewhere, but is not a peer-reviewed journal article.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations